2011
DOI: 10.1074/jbc.m111.238014
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulates Mammalian Target of Rapamycin Complex 1 (mTORC1) Activity by Modulating the TSC1/TSC2-Rheb GTPase Pathway

Abstract: Mammalian target of rapamycin (mTOR) is a kinase that plays a key role in a wide array of cellular processes and exists in two distinct functional complexes, mTOR complex 1 (mTORC1) and mTOR complex 2 (mTORC2). Although mTORC2 is primarily activated by growth factors, mTORC1 is regulated by numerous extracellular and intracellular signals such as nutrients, growth factors, and cellular redox. Previous study has shown that cysteine oxidants sufficiently activate mTORC1 activity under amino acid-depleted conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
116
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 58 publications
7
116
1
Order By: Relevance
“…Consistent with this, a redox-sensitive formation of TORC1 and its signaling function was suggested [19][20][21][22]. Analysis of the FATC sequence with the program e-motif (G. Tevzadze personal communication) suggested that the C-terminal end that is rich in aromatic residues (Fig.…”
Section: Introductionmentioning
confidence: 61%
“…Consistent with this, a redox-sensitive formation of TORC1 and its signaling function was suggested [19][20][21][22]. Analysis of the FATC sequence with the program e-motif (G. Tevzadze personal communication) suggested that the C-terminal end that is rich in aromatic residues (Fig.…”
Section: Introductionmentioning
confidence: 61%
“…In addition, PTEN, which removes the 3’ phosphate from PIP 3 and thus opposes PI3K activity, is likewise inhibited by ROS (Lee et al ., 2002; Leslie et al ., 2003; Connor et al ., 2005). Finally, ROS inhibits the Tsc1/Tsc2 complex, thereby relieving Tor from upstream inhibition (Yoshida et al ., 2011). Thus, ROS acts through a variety of targets to activate IIS and Tor.…”
Section: A Proposed Mechanism For the Mitochondrial Death Spiralmentioning
confidence: 99%
“…In addition, the lysosomal re-localization of TSC complex is also an important stress response to inhibit mTORC1-mediated growth and the presence of any single stress maintains TSC complex at the lysosomes (Demetriades et al, 2016). Rheb-mTORC1 is also able to sense the cellular redox state (Patel and Tamanoi, 2006;Di Nardo et al, 2009;Yoshida et al, 2011) which occurs independent of the amino acid levels and the Rag-regulator system. In addition to TSC complex, there are other upstream regulators for Rheb.…”
Section: Regulation Of Rheb Signaling Pathway By Subcellular Localizamentioning
confidence: 99%